PEMBUATAN PESTISIDA MENGGUNAKAN TEMBAKAU - Mellisa Fitri (UII, 2014)
Dusun Kaisat,Selomirahvillage, District Ngablak, Magelang, Central Java.Mostlylivelihood society is a farmer.One of problems that faced by farmers of Dusun Kalisatbeside the rare of some fertilizer and seeds are also a problem in controlling pests.Difficulties in pest control problems are with the high price of synthetic pesticides ororganic. Required an important breakthrough to solve the problem of this pesticide,One solution is the use of botanical pesticides, namely pesticides are based from naturesuch as plants. One of agricultural products is very abundant and can be exploited is thetobacco plant. Dusun Kalisat community can utilize the waste tobacco which did notused to make a pesticide plant.